Immunogenicity and safety of the 13-valent Pneumococcal Conjugate vaccine in 23-valent pneumococcal polysaccharide vaccine-naive and pre-immunized patients under treatment with chronic haemodialysis: a longitudinal quasi-experimental phase IV study. (January 2018) - Vandecasteele, S.J.; De Bacquer, D.; Caluwe, R.; Ombelet, S.; Van Vlem, B.
Abstract: Objective: To benchmark the immunogenicity of pneumococcal conjugated vaccine (PCV-13) versus pneumococcal polysaccharide vaccine (PPV-23) in haemodialysis patients pre-vaccinated or not with PPV-23. Methods: The study is a longitudinal quasi-experimental phase IV study in chronic haemodialysis patients aged ≥50 years. Total (ELISA) and functional (opsonophagocytic assay) antibodies after pneumococcal vaccination were quantified at baseline, and after 28 and 365 days. Of 201 eligible patients, 155 were included. Patients were divided in four groups. PPV-23 naive patients were randomized to PPV-23 (40) or PCV-13 (40) vaccination. PPV-23-pre-vaccinated patients were categorized as being vaccinated more (40) or less (35) than 4 years before the study and all received PCV-13. Results: Patients among the four groups had a significant ELISA antibody response for most serotypes that remained significant up to day 365 versus baseline. In PPV-23-naive patients, ELISA antibody titres were significantly higher among PCV-13 versus PPV-23 recipients for six serotypes (1.85–2.34-fold) after 28 days, and remained significantly higher for one serotype (6A, 1.57-fold) after 365 days. Following PCV-13 vaccination, increase in ELISA antibody titres was significantly higher among PPV-23-naive versus PPV-23-pre-vaccinated patients for 12 serotypes after 28 days (1.68–7.74-fold) and remained significantly higher in ten serotypes (1.44–3.29-fold) after 365 days. Conclusion: Immune response after PPV-23 and PCV-13 remains significant for at least 1 year in non-PPV-23-pre-vaccinated patients. Among vaccine-naive haemodialysis patients PCV-13 seems more immunogenic than PPV-23. Immune response to PCV-13 is weaker in PPV-23-pre-vaccinated compared with vaccine-naive patients.